Obesidade e acompanhamento nutricional: percepções da criança em um programa de educação nutriconal - Kanashiro, Thais de Oliveira Mendes (2020)
In the last three decades, it was possible to show that the world is going through a nutritional transition process, characterized by a reduction in malnutrition and an increase in overweight and obesity. Nutritional monitoring is therefore extremely important for the treatment of childhood obesity, since obesity can lead to physiological, social and psychological consequences. Considering the child as a subject of rights and the legitimacy of his voice, it is proposed in this research to provide the child with obesity to become the protagonist of his treatment. The children were accompanied by the care of a nutritionist in order to reduce weight and increase quality of life, without creating pressure or restrictions. The objective of the study was to investigate the perception of 5 (five) children, between 8 and 12 years old, diagnosed with obesity, about their eating habits before and during four months of nutritional monitoring, focusing on what they tell about what whether or not it promotes changes during treatment. This study has a quantitative and qualitative design and uses several instruments for the construction of empirical data. From a qualitative point of view, narrative interviews were used; child's food diary; drawings of the child and guardian. From a quantitative point of view, anthropometric assessments were analyzed. The analyzes are based on the interpretation of empirical data in the light of symbolic aspects, compatible with the evolution of anthropometric measures. The children did not achieve a significant reduction in weight, however, during the short treatment period, significant changes in the eating behavior of children were observed, that despite wanting to modify their eating habits, their family members were not engaged enough to do so. In conclusion, the results reveal the importance of the child's perception in nutritional monitoring as an innovative way to treat childhood obesity.